Economics, Darwinism, and the Case of Disciplinary Imports. (20th December 2012) - Cojanu, Valentin
Abstract The problem of causality in economics is still contended by various epistemological alternatives. The article builds on the received view of Darwinism in economics and examines the way in which economics and biology find common ground in concepts and assumptions that reflect causal commonalities of the natural and the social world. We claim that the role the contingent pattern plays in understanding socioeconomic change provides reasons to concede corrections to a rule‐based causal mechanism. The article concludes on the merits of advancing the ontological equivalent of interdisciplinary studies as one possible standard in reference to which to judge the epistemic adequacy of any import.